Radioimmunoconjugates for treating cancer: recent advances and current opportunities. (3rd July 2017) - Bourgeois, Mickaël; Bailly, Clément; Frindel, Mathieu; Guerard, François; Chérel, Michel; Faivre-Chauvet, Alain; Kraeber-Bodéré, Françoise; Bodet-Milin, Caroline
ABSTRACT: Introduction : Radioimmunoconjugates have been used for 30 years to diagnose and treat cancer. For many years, the use of these therapeutic tools has been limited to haematological disorders, such as non-Hodgkin's lymphoma, given that they have only had a moderate effect on solid tumours. Areas covered : Recently, several strategies have revived the potential therapeutic application for radioimmunoconjugates. In this review, the authors review the advances in immunological engineering to develop new tools like monoclonal antibodies and their derivatives. Then, the authors summarize the development of radionuclides, the use of recombinant antibodies, pretargeting approaches, and dose fractionation techniques, providing opportunities for both therapeutic and diagnostic applications. Expert opinion : Radioimmunoconjugates used in nuclear medicine have entered a new era of development. These advances give rise to a variety of opportunities in the management of various cancers, where the radiolabelled antibodies may be particularly useful in immuno-specific phenotypic imaging e.g. companion diagnostics. Concerning therapeutic applications, radioimmunoconjugates have demonstrated their efficacy in the treatment of both haematological malignancies and solid tumours. Recent procedural developments are of great interest in optimising oncological targeted therapies. In the field of cancer theranostics, we believe that radioimmunoconjugated compounds are likely to play a large part in near future.